Thermodynamic assessment of (semi-)volatile hydrophobic organic chemicals in WWTP sludge – combining solid phase microextraction with non-target GC/MS. Issue 12 (25th October 2018) - Knudsmark Sjøholm, Karina; Flyckt-Nielsen, Matias; Bucheli, Thomas D.; Mayer, Philipp
Abstract : Equilibrium HS-SPME non-target GC/MS assessment of chemical potential of (semi-)volatile HOCs across treatment processes revealed increase from inlet to digested sludge, and effective reduction of the exposure level by co-composting. Abstract : Applying WWTP sludge on arable soil has clear benefits from a resource recycling point of view but can potentially also lead to contamination of soil, agricultural products and the environment. The sludge contains a complex mixture of particularly hydrophobic organic chemicals (HOCs) that sorb to the organic matter. Equilibrium sampling was recently applied to the measurement of chemical activities of polycyclic aromatic hydrocarbons (PAHs) in secondary and digested sludge, and clear activity increases due to the anaerobic digestion treatment were observed. In the present study we extend this work to a large number of (semi-)volatile HOCs by combining automated headspace solid phase microextraction with non-targeted gas chromatography mass spectrometry. Chemical activity ratios were determined between sludge from the different stages of a WWTP and after co-composting with garden waste and sorbent amendment with activated carbon (AC) and biochar (BC). Generally, chemical activities increased from primary, to secondary, to digested sludge and the level in the dewatered sludge was not significantly different from the level in the digested sludge. Decamethylcyclopentasiloxane (D5) behaved differently as the level was similar until the dewatering step, where it increased 4-fold. The results confirmed the earlier observation that anaerobic digestion increased chemical activity, now for a broader range of chemicals, and showed that co-composting was effective in reducing chemical activities of most of the tested (semi-)volatile organic chemicals. Of the studied compounds, activities of D5 and a musk fragrance were reduced the least by co-composting.